2021
DOI: 10.3389/fonc.2021.630717
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Survival of Patients With Advanced Non-Small Cell Lung Cancer Guided by Comprehensive Genomic Profiling: Real-World Single-Institute Study in China

Abstract: Although the National Comprehensive Cancer Network and the Chinese Society of Clinical Oncology guidelines recommend comprehensive genomic profiling of lung adenocarcinoma, it has not been widely applied in Chinese hospitals. This observational study aimed to determine real-world evidence of whether comprehensive genomic profiling can benefit the survival of patients with lung cancer. We investigated the frequency of genomic alterations, treatment strategies, and clinical outcomes in 233 patients with advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
2
1
Order By: Relevance
“…We identified 556 variants, with 416 potentially actionable variants in 54.88% (309/563) patients. The percentage of patients harboring actionable genetic alterations is slightly lower than the previous studies (62%) (31). This is due to the small target gene panel.…”
Section: Discussioncontrasting
confidence: 66%
“…We identified 556 variants, with 416 potentially actionable variants in 54.88% (309/563) patients. The percentage of patients harboring actionable genetic alterations is slightly lower than the previous studies (62%) (31). This is due to the small target gene panel.…”
Section: Discussioncontrasting
confidence: 66%
“…Similar inferior survival benefits were also found in several studies for specific concomitant EGFR mutations, including MET amplification, PTEN deletion, TP5 3 mutation, and PIK3CA mutations [55–59] . However, Labbé et al [60] found no significant survival difference associated with TP53 status in EGFR -mutant patients administered both first- and third-generation EGFR-TKIs, except patients with concomitant TP53 missense mutations (PFS: HR = 1.91, 95% CI: 1.01–3.60, P = 0.04).…”
Section: Egfr Concomitant Mutationssupporting
confidence: 64%
“…[53] Besides, Jiang et al [54] Similar inferior survival benefits were also found in several studies for specific concomitant EGFR mutations, including MET amplification, PTEN deletion, TP53 mutation, and PIK3CA mutations. [55][56][57][58][59] However, Labbé et al [60] found no significant survival difference associated with TP53 status in EGFR-mutant patients administered both firstand third-generation EGFR-TKIs, except patients with concomitant TP53 missense mutations (PFS: HR = 1.91, 95% CI: 1.01-3.60, P = 0.04). A phase Ib/II study also showed that patients with advanced EGFR mutations with concomitant TP53 mutations had PFS comparable to that of patients with wild-type TP53 (14.0 months vs. 15.4 months, P = 0.32) who received the novel second-generation EGFR-TKI mefatinib.…”
Section: Monotherapymentioning
confidence: 99%
“…In 2020, the Chinese Society of Clinical Oncology (CSCO) guidelines approved aumolertinib as a second-line treatment for patients with advanced NSCLC and T790M mutation. In 2021, CSCO guidelines recommended aumolertinib as a first-line treatment for patients with advanced NSCLC and EGFR-sensitive mutations ( 7 ). Recently, some reports have emerged on the alternatives for overcoming resistance to osimertinib, such as use of brigatinib alone or in combination with cetuximab ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%